Deformation twinning in rolled WE43-T5 rare earth magnesium alloy: Influence on strain hardening and texture evolution. (1st June 2017) - Jahedi, Mohammad; McWilliams, Brandon A.; Moy, Paul; Knezevic, Marko
Abstract: Insights from a detailed investigation into the anisotropic strain hardening, tension/compression yield asymmetry, and evolution of crystallographic texture of rolled WE43 rare earth magnesium alloy during quasi-static tension and compression at room temperature are presented in this paper. It is seen that WE43 exhibits monotonically falling normalized strain hardening rates during both tension and compression in multiple loading directions, which is unusual for Mg alloys. Moreover, the difference in strain hardening in tension and compression subsequent to initial yield is observed to be very small and, as a result, the tension/compression asymmetry is not pronounced. Nevertheless, crystallographic texture evolves substantially, where crystals before deformation oriented with their crystallographic c -axis parallel with the normal direction (ND) and slightly tilted towards the rolling direction (RD) of the plate reorient their c -axis nearly parallel to the compression direction for every testing direction. Amount of deformation twinning in WE43 with plastic strain is quantified here for the first time and correlated with the above-described aspects of plastic deformation and texture evolution. In doing so, we confirm that the 10 1 ¯ 2 1 ¯ 011 twin is the preferred extension twin in WE43 just like in many Mg alloys. Besides, we find a substantial activity of another c -axis extension twinning mode 11 2 ¯ 1 1 ¯ 1 ¯ 26 in WE43, which is another unusual observation for Mg alloys. Activity of the c -axis contraction twins was found to be negligible. The falling strain hardening rates in WE43 are rationalized here to be a consequence of: (1) modest texture hardening because the activation stress for pyramidal slip systems is similar in magnitude to those of basal and prismatic slip systems, (2) small Hall-Petch-like hardening effect due to extension twinning because of their transmissivity to slip and rapid growth, and (3) negligible Hall-Petch-like hardening effect due to contraction twinning because of their small activity. Graphical abstract: Image 1